Partial-volume correction increases estimated dopamine D2-like receptor binding potential and reduces adult age differences. Issue 5 (May 2019) - Smith, Christopher T; Crawford, Jennifer L; Dang, Linh C; Seaman, Kendra L; San Juan, M Danica; Vijay, Aishwarya; Katz, Daniel T; Matuskey, David; Cowan, Ronald L; Morris, Evan D; Zald, David H; Samanez-Larkin, Gregory R
The relatively modest spatial resolution of positron emission tomography (PET) increases the likelihood of partial volume effects such that binding potential (BPND ) may be underestimated. Given structural grey matter losses across adulthood, partial volume effects may be even more problematic in older age leading to overestimation of adult age differences. Here we examined the effects of partial volume correction (PVC) in two studies from different sites using different high-affinity D2-like radioligands (18 F-Fallypride, 11C-FLB457) and different PET camera resolutions (∼5 mm, 2.5 mm). Results across both data sets revealed that PVC increased estimated BPND and reduced, though did not eliminate, age effects on BPND . As expected, the effects of PVC were smaller in higher compared to lower resolution data. Analyses using uncorrected data that controlled for grey matter volume in each region of interest approximated PVC corrected data for some but not all regions. Overall, the findings suggest that PVC increases estimated BPND in general and reduces adult age differences especially when using lower resolution cameras. The findings suggest that the past 30 years of research on dopamine receptor availability, for which very few studies use PVC, may overestimate effects of aging on dopamine receptor availability.